No effect of muscle stretching within a full, dynamic warm-up on athletic performance - Blazevich, A. J.; Gill, N. D.; Kvorning, T.; Kay, A. D.; Goh, A. G.; Hilton, B.; Drinkwater, E. J.; Behm, D. G. (Medicine & Science in Sports & Exercise, 2018)
Purpose This study aimed to examine the effects of static and dynamic stretching routines performed as part of a comprehensive warm-up on flexibility and sprint running, jumping, and change of direction tests in team sport athletes.